2022
DOI: 10.1093/neuonc/noac193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic validation of a new classification system for extent of resection in glioblastoma: A report of the RANO resect group

Abstract: Background Terminology to describe extent of resection in glioblastoma is inconsistent across clinical trials. A surgical classification system was previously proposed based upon residual contrast-enhancing (CE) tumor. We aimed to (I) explore the prognostic utility of the classification system and (II) define how much removed non-CE tumor translates into a survival benefit. Methods The international RANO resect group retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 35 publications
4
79
0
Order By: Relevance
“…With approval of the ethics committee of the Ludwig-Maximilians-University (Munich, Germany; AZ-21-0996), the RANO resect group compiled a retrospective database of newly diagnosed IDH -wildtype glioblastomas treated between 2003 and 2022 with a follow-up of ≥3 months. 5 For the current study, individuals were selected when information on TERT promotor mutation status was available for review. Demographics, molecular information, clinical data, and outcome were extracted; and date of progression was determined per RANO criteria.…”
mentioning
confidence: 99%
“…With approval of the ethics committee of the Ludwig-Maximilians-University (Munich, Germany; AZ-21-0996), the RANO resect group compiled a retrospective database of newly diagnosed IDH -wildtype glioblastomas treated between 2003 and 2022 with a follow-up of ≥3 months. 5 For the current study, individuals were selected when information on TERT promotor mutation status was available for review. Demographics, molecular information, clinical data, and outcome were extracted; and date of progression was determined per RANO criteria.…”
mentioning
confidence: 99%
“…In most cases, no residual tumor volume was detected on immediate postoperative (postOP) MRI with median postoperative CE tumor volume 0.0 ± 0.4 cm 3 (range: 0–24 cm 3 ) and median postoperative non-CE T2-FLAIR lesion volume 0.0 ± 1.6 cm 3 (range: 0–64 cm 3 ). In detail, residual tumor volumes were allocated to their respective RANO resect classes for EOR in glioblastoma [ 3 ]. Here, supramaximal CE resection (class 1) was achieved in 36/64 patients (56%), maximal CE resection (class 2) was possible in 15/64 patients (23%), and the remaining 13/64 patients (20%) underwent submaximal CE resection (class 3; Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…For all patients, we routinely applied a macrocyclic gadolinium-based contrast agent (gadoteric acid, Dotagraf 0.5 mmol/mL; 0.2 mL/kg bodyweight; 0.1 mmol/kg; flow rate 1 mL/s). Volumetric image analyses were performed as previously described [ 3 ]. In short, tumor volumes were quantified by ceT1-weighted and FLAIR (or if not available, T2)-sequences on pre-/postoperative and pre-radiotherapy MRI scans using commercially available imaging software (BrainLab ® Elements; Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, expanding surgical margins is not always feasible because the peritumor can extend to eloquent areas, thus increasing the risk of postoperative neurological deficits. The Response Assessment in Neuro-Oncology (RANO) group recently concluded that less than 5 mL residual non-enhancing tumor volume is prognostically better than complete resection of contrast-enhancing volume alone [ 9 ]. However, the non-enhancing tumor varies in size and location, and a more tailored approach toward the non-enhancing tumor burden could be beneficial.…”
Section: Introductionmentioning
confidence: 99%